THE EFFECT OF TECHNICAL ANALYSIS ON CRYPTOCURRENCY INVESTMENT RETURNS WITH THE 5 (FIVE) HIGHEST MARKET CAPITALIZATIONS IN INDONESIA - Rico Nur Ilham; Irada Sinta; Mangasi Sinurat (Jurnal Ekonomi, 2022)
This study aims to determine the effect of asset price, asset volume and asset supply on cryptocurrency investment returns with the 5 (five) highest market capitalizations in Indonesia. The population in this study were all coins registered on the indodax exchange service and samples were taken using the purposive sampling method with a total sample of 5 crypto coins. The data analysis method used is multiple linear analysis. The results of this study partially indicate that asset price has a significant effect on returns with a significant value of 0.0197 0.05 with a tcount value of (1.235478) < ttable (1.65356), asset volume has no significant effect on returns with a significant value of 0.3833> 0.05 with a tcount value (-0.874042 ) < ttable ( 1.65356),